Microlearning and its Effectiveness in Modern Education: A Mini Review - Mostrady, Ahmed; Sanchez-Lopez, Eva; Gonzalez-Sanchez, Andres Filipe (Tecno Scientifica Publisher, 2025)
The modern educational environment is increasingly moving toward using innovative teaching approaches. One such approach is microlearning, which is characterized by delivering small, focused portions of information that can be quickly consumed and easily retained. Microlearning fits well within the context of digitized education. Its flexibility and adaptability make it a good match for the kinds of short, attention-limited spans that today's learners tend to have. This review will look at the concept of microlearning, the technological platforms that can be used for it, and the effectiveness of microlearning for improving learning outcomes. Several studies have shown that microlearning improves knowledge retention, lowers cognitive load, and allows learners to consume content at their own pace. These studies have established microlearning as a highly effective and flexible modern pedagogical practice. The dissemination of microlearning is now largely in the hands of digital tools—mobile apps, e-learning platforms, and social media—making it more accessible and convenient than ever before. In conclusion, microlearning presents a promising model for modern education, offering substantial cognitive benefits when applied effectively. However, it is essential to balance its use with more in-depth learning strategies to ensure comprehensive understanding.